Fuel Consumption Efficiency in Construction Equipment Operations: A Mixed Methods Analysis of Determinants and Practices - Gabriel, John Alvin M.; Narsico, Peter G. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study examines the key factors affecting fuel consumption efficiency in construction equipment operations. Using a mixed methods approach, it combines quantitative regression analysis with qualitative interviews of equipment operators. A survey was conducted to gather data on operator behavior, equipment maintenance, equipment condition, worksite environment, and operator experience and training. Regression results showed that among these factors, only operator experience and training significantly predicted fuel efficiency, with R² = .31. Other variables, such as operator behavior, maintenance practices, equipment condition, and worksite environment, were not statistically significant predictors. Qualitative interviews supported these findings. Operators emphasized the importance of situational awareness, experience, and task-specific adjustments in saving fuel. Common strategies included managing engine RPM according to workload, shutting down equipment during idle periods, and using neutral gear on downhill slopes when safe. These practices rely more on operator judgment than on technical specifications. While maintenance, equipment condition, and environmental factors were frequently mentioned, their influence appears indirect or context-dependent. This suggests that technical improvements alone are insufficient without skilled operator input. The study concludes that operator training and experience, play a central role in fuel efficiency. It recommends that construction firms invest in targeted training and behavior-based monitoring to promote sustainable and efficient equipment use.